Pengenalan dan Pemanfaatan Tanaman Obat Keluarga (TOGA) Sebagai Upaya Mengoptimalkan Karakter Tanggung Jawab Remaja - Syarifah Masthura; Nursaadah Nursaadah; M. Nuril Hadi; Rian Ramadhan; Nadiatul Zara; Dian Muspita Sari (Pusat Riset dan Inovasi Nasional, 2025)
Adolescence is a crucial developmental phase often marked by a lack of responsibility, which can lead to negative behaviors such as juvenile delinquency and promiscuity. Therefore, developing a responsible character in adolescents is essential to guide them toward positive behavior. One effective approach is through life skills education implemented in the local village (gampong) environment. This community service initiative aims to instill a sense of responsibility in adolescents by involving them in the planting and maintenance of family medicinal plants (TOGA). Through this activity, adolescents are expected to develop care, discipline, and responsibility, which are reflected in their commitment to nurturing the plants. The activity was implemented in Gampong Cot Alue, Ingin Jaya District, Aceh Besar, and carried out over two days, from February 14 to 15, 2025. The method used in the planning and execution of the TOGA planting involved five stages: (1) creating an activity plan, (2) preparing tools and materials, (3) preparing the planting area, (4) plant nurseries, and (5) creating plant identification markers. These stages were designed to introduce a structured approach to life skills and community engagement.The outcomes of the program demonstrated an increase in adolescents' awareness and understanding of the importance of TOGA. Additionally, there was a noticeable improvement in their sense of responsibility and participation in daily activities beyond school. The broader community, particularly the youth, gained valuable knowledge about the benefits of TOGA for disease prevention, treatment, and health maintenance, contributing to a healthier and more proactive lifestyle within the village environment.